Pelaksanaan cuci tangan pakai sabun dan kaitannya dengan kejadian phlebitis di ruang rawat inap RS Harapan Bunda Banda Aceh - Zibmi Rahmi; Rika Andriani (Nur Science Institute, 2023)
The most common complication from infusion is phlebitis, one of which can occur because the hand are not free from germs during infusion. The research was conducted with the aim of knowing and analyzing the relationship between washing hands with soap and the incidence of phlebitis in patient room of Rumah Sakit Harapan Bunda Banda Aceh. This research method is correlative analytic with a cross sectional study approach with a total sample of 93 respondents using accidental sampling technique. The data collection instrument was an observation sheet consisting of 6 observation items of handwashing with soap, and an observation sheet of phlebitis events. Research data collection began on December 21 2022 to January 6 2023 in the Inpatient Room of Rumah Sakit Harapan Bunda Banda Aceh. The results of the study based on the chi square test showed a p-value = 0.000. The results of the study was found that there was a significant relationship between the variables of handwashing with soap and the incidence of phlebitis in patients in the Inpatient Room of Rumah Sakit Harapan Bunda Banda Aceh. It is expected that nurses always apply 6-step hand washing at all 5 moments of hand washing, especially before infusion.